THE INFLUENCE OF ISLAMIC CORPORATE GOVERNANCE (ICG), COMPANY SIZE, AND LEVERAGE (DAR) ON FINANCIAL PERFORMANCE (ROA) IN SHARIA PEOPLE'S FINANCING BANKS IN INDONESIA - Rana Shabilah; Achmad Fauzi; Indah Muliasari (CURRENT ADVANCED RESEARCH ON SHARIA FINANCE AND ECONOMIC WORLDWIDE, 2023)
This study aims to assess how Islamic Corporate Governance (ICG), bank size, and leverage (DAR) influence financial performance using Return on Assets (ROA) as a measure. The study focuses on Sharia Rural Banks (BPRS) registered with the Financial Services Authority (OJK) from 2021 to 2022. The sample includes 99 BPRS selected through purposive sampling. The analysis employs multiple linear regression via SPSS software. The findings reveal that ICG has no significant impact on BPRS's financial performance (ROA). Conversely, firm size positively affects ROA, while leverage (DAR) has a negative impact. Future research could encompass various types of Sharia banks and include additional indicators like Return on Equity (ROE) and Return on Investment (ROI). Extending the study's timeframe might provide more accurate insights into trends. Furthermore, incorporating additional proxies to measure bank financial performance, such as Return on Equity (ROE) and Return on Investment (ROI), is advised. A more extended study duration would likely yield a more accurate representation of trends and relationships.